Penanaman Pendidikan Karakter Empati dalam Pembelajaran Sejarah di SMA IT Granada Samarinda - Nurkhadijah, Yunita; Rahuma, Aulia (STKIP PGRI SITUBONDO, 2024)
This study aims to determine the cultivation of empathy character education in history learning and to find out the obstacles faced by teachers in cultivating empathy character education in history learning at SMA IT Granada Samarinda. This research uses qualitative research with phenomenological studies through observation, interviews and documentation. The results showed that character-based learning planning, the material used by history teachers regarding the events of November 10 with an open learning model Open Ended Learning (OEL). The strategy applied by history teachers in instilling empathy character education by providing exemplary examples. The core activities in the implementation of learning include the teacher's explanation of the events of the struggle of KH. Hasyim Asy'ari and Bung Tomo, followed by discussion, question and answer, conclusion and evaluation. The obstacles faced by history teachers in the implementation of learning include lack of student attention in class, lack of student understanding related to empathy, lack of teaching variations and lack of teacher skills in designing character-based learning.